Effect of hyperproduction of TEM-1 beta-lactamase on in vitro susceptibility of Escherichia coli to beta-lactam antibiotics. - Wu, P J (1994)
The susceptibility of 173 TEM-1-producing isolates of Escherichia coli was assessed by determination of MICs by the agar dilution method. MICs of amoxicillin, mezlocillin, cephaloridine, and, to a smaller extent, amoxicillin-clavulanic acid (but not cephalexin, cefuroxime, cefotaxime, ceftazidime, or imipenem) were higher for isolates that produced large amounts of beta-lactamase than for isolates that produced smaller amounts. The effect of fixed concentrations of clavulanic acid on resistance to amoxicillin was assessed for 34 selected TEM-1-producing isolates. Low concentrations of the inhibitor (0.5 to 1 microgram/ml) reduced the amoxicillin MICs substantially for almost all the isolates, although the reductions were not sufficient to render any of the isolates amoxicillin susceptible. Higher concentrations of clavulanic acid had progressively greater effects on amoxicillin MICs, but even at 8 micrograms/ml some of the isolates with high beta-lactamase activities remained resistant or only moderately susceptible to amoxicillin. All the isolates were inhibited by clavulanic acid (in the absence of amoxicillin) at concentrations of 16 to 32 micrograms/ml. TEM-1 beta-lactamase activity was inhibited in vitro by clavulanic acid, but not totally, with approximately 2% of the initial activity remaining at 2 micrograms/ml and 0.4% remaining at 8 micrograms/ml. These findings suggest that the amount of beta-lactamase activity is a major determinant of the degree of resistance to several beta-lactam antibiotics and can make the difference between susceptibility and resistance to some compounds, notably the combination of amoxicillin with clavulanic acid.